Effects of Peatland Fires on Above-ground Carbon Stocks in Kepulauan Meranti Regency, Riau Province - Cahyaningtyas, Anggita Utami; Setiawan, Yudi; Putra, Erianto Indra; Tonoto, Prayoto (Institut Pertanian Bogor (IPB University), 2024)
Peat fires substantially alter ecosystem dynamics and carbon storage, making it essential to understand how fire-related components affect post-fire carbon stocks. This study aims to estimate the above-ground carbon stock on burned peatlands in Kepulauan Meranti Regency, Riau Province, and examine how fire recurrence, last fire occurrence, and burn severity influence the carbon stock using a modified regression model and remote sensing data. The normalized burn ratio index difference between post- and pre-fire was used to calculate burn severity. The continuous predictor variable was transformed using a natural logarithm to generate the best-fit model. The 2014 burned peatland stored the highest carbon, whereas the 2020 burned peatland was the lowest. The 2020 fire period was the most severe compared to the 2014 and 2018–2019 fires, although it had a smaller burned area. This study highlights that fire-related components significantly affect post-fire peatland above-ground carbon stocks, particularly last fire occurrence and burn severity. Meanwhile, fire recurrence had the weakest impact and correlation with above-ground carbon stock compared to other predictors, likely due to the brief intervals between fire events in 2018 and 2019, which may have restricted ecosystem recovery and limited carbon storage capacity.